Development and Examination of the Reactive Attachment Disorder and Disinhibited Social Engagement Disorder Assessment Interview. (June 2020) - Lehmann, Stine; Monette, Sebastien; Egger, Helen; Breivik, Kyrre; Young, David; Davidson, Claire; Minnis, Helen
The fifth edition of the Diagnostic and Statistical Manual ( DSM ) categorizes reactive attachment disorder (RAD) and disinhibited social engagement disorder (DSED) as two separate disorders, and their criteria are revised. For DSED, the core symptoms focus on abnormal social disinhibition, and symptoms regarding lack of selective attachment have been removed. The core symptoms of RAD are the absence of attachment behaviors and emotional dysregulation. In this study, an international team of researchers modified the Child and Adolescent Psychiatric Assessment for RAD to update it from DSM-IV to DSM-5 criteria for RAD and DSED. We renamed the interview ther eactive attachment disordera ndd isinhibited social engagement disordera ssessment (RADA). Foster parents of 320 young people aged 11 to 17 years completed the RADA online. Confirmatory factor analysis of RADA items identified good fit for a three-factor model, with one factor comprising DSED items (indiscriminate behaviors with strangers) and two factors comprising RAD items (RAD1: failure to seek/accept comfort, and RAD2: withdrawal/hypervigilance). The three factors showed differential associations with clinical symptoms of emotional and social impairment. Time in foster care was not associated with scores on RAD1, RAD2, or DSED. Higher age was associated with lower scores on DSED, and higher scores on RAD1.